Complex interventions of abdominal aorta and its branches in children with Takayasu arteritis: Clinical experience from a tertiary care center in north‐west India. (5th November 2018) - Vijayvergiya, Rajesh; Jindal, Ankur K.; Pilania, Rakesh K.; Suri, Deepti; Gupta, Anju; Sharma, Ashish; Sinha, Saroj K.; Singhal, Manphool; Bahl, Ajay; Singh, Surjit
Abstract: Aim: To report our experience on complex percutaneous interventions of the abdominal aorta and its branches in six children with Takayasu arteritis (TA). Methods: A review of records of children with TA, who underwent percutaneous interventions of the abdominal aorta and its major branches. Results: In this analysis, we included six children with TA who underwent intervention of the abdominal aorta and its major branches. The endovascular interventions were performed mostly for treatment‐resistant renovascular hypertension and mesentery artery ischemia. Mean age (±SD) at time of intervention was 10.6 ± 2.5 years (four boys and two girls). Percutaneous interventions included stenting of abdominal aorta (n = 2), renal arteries (n = 4), mesenteric arteries (n = 2), repeat stenting for renal artery in‐stent restenosis (n = 1), and renal autotransplantation (n = 4). All 13 interventions were successful and enabled us to obtain good control of blood pressure. Conclusion: We hereby report six children with TA who were successfully managed with complex percutaneous interventions of the abdominal aorta and its major branches. Balloon dilatation and stent placement constitutes the mainstay of management of TA with stenosis of the large vessels.